Measurement of the W boson polarisation in [Formula: see text] events from pp collisions at [Formula: see text] = 8 TeV in the lepton + jets channel with ATLAS - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al. (The European physical journal. C, Particles and fields, 2017)
This paper presents a measurement of the polarisation of W bosons from [Formula: see text] decays, reconstructed in events with one high-[Formula: see text] lepton and at least four jets. Data from pp collisions at the LHC were collected at [Formula: see text] = 8 TeV and correspond to an integrated luminosity of 20.2 fb[Formula: see text]. The angle [Formula: see text] between the b-quark from the top quark decay and a direct W boson decay product in the W boson rest frame is sensitive to the W boson polarisation. Two different W decay products are used as polarisation analysers: the charged lepton and the down-type quark for the leptonically and hadronically decaying W boson, respectively. The most precise measurement of the W boson polarisation via the distribution of [Formula: see text] is obtained using the leptonic analyser and events in which at least two of the jets are tagged as b-quark jets. The fitted fractions of longitudinal, left- and right-handed polarisation states are [Formula: see text], [Formula: see text] and [Formula: see text], and are the most precisely measured W boson polarisation fractions to date. Limits on anomalous couplings of the Wtb vertex are set.